Spending when illiquid savings become liquid: Evidence from Danish wage earners - Henrik Yde Andersen (Danmarks Nationalbank, 2020)
This paper offers new empirical evidence on the marginal propensity to consume out of an unanticipated liquidity shock. A Danish 2012 policy reform reduced the incentive to retire early in order to increase labour supply but at the same time the policy released a substantial amount of savings from an early retirement scheme that were locked in the scheme until the policy change. By exploiting the fact that cohorts were affected differentially by the policy, this paper uses a difference-indifferences specification to estimate an average increase in the propensity to spend of 43 per cent. The estimated spending patterns are consistent with the notion of wealthy hand-to-mouth behaviour.
Keywords: D14; D15; E21; H31; E62; 330; Economic activity and employment; Householdbalance sheets; Public finances and fiscal policy